Clinical characteristics and survival outcomes in patients aged 75 years or older with advanced colorectal cancer treated using traditional Chinese medicine: an observational retrospective study - Wu, Jiao; Cui, Ning; Li, Zhongyu; Wu, Yu; Hao, Tengteng; Li, Liusheng (Frontiers in Pharmacology, 2023)
Abstract: Limited evidence suggests that elderly patients with advanced colorectal cancer (ACRC) may benefit from traditional Chinese medicine (TCM). This study investigated the efficacy and safety of TCM in patients aged ≥75 years with ACRC treated in the Oncology Department of Xiyuan Hospital between January 2012 and December 2021. The clinical characteristics of these patients were retrospectively reviewed. Their progression-free survival (PFS) and total duration of TCM therapy (TTCM) were analyzed using the Kaplan-Meier method. Forty-eight patients (35 male, 13 female) with a mean age of 78.75±2.99 years (range, 75–87) met the inclusion criteria. There were 18 cases of rectal cancer and 30 of colon cancer. The median PFS was 4 months (range, 1–26; 95% confidence interval 3.26–4.73). The median TTCM was 5.5 months (range, 1–50; 95% confidence interval 1.76–8.24). Subgroup analysis revealed that PFS and TTCM were shorter in patients with bone metastases and an ECOG performance status score of 2–3 (P<0.05). No hematological toxicity or serious adverse reactions occurred during the study period. This real-world study demonstrates that TCM can be used safely in patients with ACRC aged ≥75 years, including when the ECOG performance status score is 2-3.